COMPARISON OF FISTULECTOMY VS LIFT PROCEDURE FOR ANAL FISTULA MANAGEMENT (Journal of Medical & Health Sciences Review, 2025)
Background: Although anal fistulae are benign, the condition can still negatively influence a patient’s quality of life. Despite its long history and prevalence, anal fistula management remains one of the most challenging and controversial topics in colorectal surgery today. This study aimed to compare the management of anal fistula with LIFT procedure and Fistulectomy.Methodology: A RCT was conducted in a single surgical unit of a tertiary teaching medical college hospital in Karachi from September 2010 through April 2016. A total of 1188 patients with anal fistula were included out of taken sample, Group A (LIFT): 610 patients (70.5% male, 29.5% female); Group B (Fistulectomy): 578 patients (64.9% male, 36.1% female). All patients were followed up for a total duration of twelve weeks during the postoperative period. Patients were followed up at weekly intervals for the initial 6 weeks and at 4-week intervals for another 6 months, and then 6 months for another 5 years.  During each follow-up visit, the patient was assessed for postoperative pain, wound complication, and anal incontinence.Results: The mean age of the patients in group A was 41.11 ±7.49 while the mean age of the patients in group B was 45.03 ±7.07 (p-value 0.005). There were 70.5% males and 29.5% Females in group A, whereas 64.9% males and 36.1% female patients were in group B. Comparison of mean pain score showed statistically significant difference in group A and B (p-value